Effect of dipeptidyl peptidase-4 inhibitors on postprandial glucagon level in patients with type 2 diabetes mellitus: A systemic review and meta-analysis - Chai, Shangyu; Zhang, Ruya; Zhang, Ye; Carr, Richard David; Zheng, Yiman; Rajpathak, Swapnil; Ji, Linong (Frontiers in Endocrinology, 2022)
Aims: Hyperglucagonemia occurs in the pathogenesis of type 2 diabetes mellitus (T2DM). In this meta-analysis, we summarized the effects of DPP4 inhibitors on glucagon levels in patients with T2DM. Materials and methods: Randomized controlled trials (RCTs) comparing the influence of DPP4 inhibitors on circulating glucagon levels with placebo or other oral antidiabetic drugs (OADs) in patients with T2DM were identified by searches of Medline (PubMed), Embase (Ovid), and CENTER (Cochrane Library). Only studies reporting changes in glucagon level presented as total area under the curve (AUCglucagon) using a meal or oral glucose tolerance test were included. Results were combined using a random-effects model that incorporated potential heterogeneity among the included studies. Results: A total of 36 RCTs with moderate to high quality were included. Overall, the numbers of T2DM patients included for the meta-analyses comparing DPP4 inhibitors with placebo and other OADs were 4266 and 1652, respectively. Compared to placebo, DPP4 inhibitors significantly reduced circulating glucagon levels (standard mean difference [SMD]: -0.32, 95% CI: -0.40 to -0.24, P<0.001; I2=28%). Analysis of subgroups revealed that study characteristics had no significant effect on results, such as study design (parallel group or crossover), number of patients, mean patient age, proportion of men, baseline HbA1c, duration of diabetes, background therapy, treatment duration, or methods for glucagon measurement (all P for subgroup differences >0.05). Moreover, DPP4 inhibitors significantly reduced glucagon levels compared to other OADs (SMD: -0.35, 95% CI: -0.53 to -0.16, P<0.001; I2=66%), and the reduction in glucagon was greater in comparison with insulin secretagogues than in comparison with non-insulin secretagogues (P for subgroup difference =0.03). Conclusions: DPP4 inhibitors are effective at reducing the circulating postprandial glucagon level in T2DM patients.